2015
DOI: 10.1039/c5sc00704f
|View full text |Cite
|
Sign up to set email alerts
|

Probing the vibrational spectroscopy of the deprotonated thymine radical by photodetachment and state-selective autodetachment photoelectron spectroscopy via dipole-bound states

Abstract: High-resolution state-selective autodetachment photoelectron spectroscopy via dipole-bound states and photodetachment spectroscopy of cryogenically cooled deprotonated thymine anions are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 69 publications
9
42
0
Order By: Relevance
“…The simulation yielded a rotational temperature of T rot = 35 K, while the cryogenic trap was operated at 4.4 K measured off the trap surface using a silicon diode temperature sensor. More recent experiments on the deprotonated thymine anion gave rise to a similar rotational temperature, 157 whereas a slightly lower rotational temperature was observed for the smaller acetate anion (∼20-35 K), 158 which was the lowest rotational temperature achieved thus far in the cryogenic Paul trap. The discrepancy between the nominal trap temperature (4.4 K) and the achieved ion temperature is most likely due to the RF-heating.…”
Section: Photodetachment Spectroscopy Of Cold Anions Via Autodetacmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation yielded a rotational temperature of T rot = 35 K, while the cryogenic trap was operated at 4.4 K measured off the trap surface using a silicon diode temperature sensor. More recent experiments on the deprotonated thymine anion gave rise to a similar rotational temperature, 157 whereas a slightly lower rotational temperature was observed for the smaller acetate anion (∼20-35 K), 158 which was the lowest rotational temperature achieved thus far in the cryogenic Paul trap. The discrepancy between the nominal trap temperature (4.4 K) and the achieved ion temperature is most likely due to the RF-heating.…”
Section: Photodetachment Spectroscopy Of Cold Anions Via Autodetacmentioning
confidence: 99%
“…The potentials of resonant PES via DBS have been illustrated in a number of recent studies. [157][158][159] The resonant PES led to the definitive determination of the 0-0 detachment transition in the acetate anion, allowing the EA of the acetyloxyl radical to be accurately and unambiguously measured. 158 Autodetachment spectroscopy and resonant PE images and spectra for the deprotonated thymine and the 2-hydroxyphenoxide anions have also been reported recently, 157,159 allowing the measurements of the vibrational frequencies of the corresponding neutral radicals and further demonstrating the potentials of resonant PES via DBS as a new technique for vibrational spectroscopy of novel radical species.…”
Section: Photodetachment Spectroscopy Of Cold Anions Via Autodetacmentioning
confidence: 99%
“…Thea ssignments of all the resonances are based on the calculated vibrational frequencies (Table S2) and the vibrational autodetachment in the resonant photoelectron spectra (Figures 3a-h), which yield tautomer-specific information. We have previously shown that vibrational frequencies in the DBS are the same as those in the neutral states, [33][34][35][42][43][44] that is,t he diffuse dipole-bound electron has little effect on the neutral cores.…”
mentioning
confidence: 95%
“…[30][31][32] We have investigated autodetachment from the vibrational levels of DBS more recently for cryogenically cooled anions and obtained highly non-Franck-Condon resonant photoelectron spectra. [33][34][35] The corresponding radicals of the seven anions in Scheme 1a ll have dipole moments larger than 2.5 De xcept for the cEAOH8a radical (Table S1). Hence,e xcited DBSs are expected to be observed, allowing tautomer-specific resonant PEI to be performed.…”
mentioning
confidence: 99%
See 1 more Smart Citation